The Method of Interactive Lessons in Teaching Physics - Begmuradov Shokhzod (European Science Publishing, 2023)
The paper presents results of "non-traditional" teaching of the basic course of Physics in the first year of study at Chirchik State Pedagogical Institute, specifically teaching via interactive method enriched with problem tasks and experiments.
Keywords: physics, optics, mechanics, interactive teaching process problem task.